2018
DOI: 10.1177/0954407018764942
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into modelling passive suspension real test rig system with consideration of nonlinear friction forces

Abstract: The vital purpose of a vehicle suspension system is to isolate the car body and hence passengers, from roadway unevenness disturbances. Implementation of passive suspension systems has continuously improved disconnection from disturbances through available deflection constraints to provide maximum isolation. In the majority of relevant reported research studies, a quarter car is modelled as moving vertically straight for both a viscous damper and a stiffness spring. The motivation for this study, reported here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…This model has been able to give a more satisfactory explanation for the observation of removing the body dynamics fluctuation as was investigated by Alzughaibi et al 1 In addition, the model simulates the symmetric hysteresis loops observed at the body bearings undergoing forcing inputs. In general, this friction model considers the static, stiction region and dynamic friction, which consists of Stribeck effect, Coulomb friction and viscous friction.…”
Section: Nonlinear Friction Forces Modelmentioning
confidence: 86%
See 2 more Smart Citations
“…This model has been able to give a more satisfactory explanation for the observation of removing the body dynamics fluctuation as was investigated by Alzughaibi et al 1 In addition, the model simulates the symmetric hysteresis loops observed at the body bearings undergoing forcing inputs. In general, this friction model considers the static, stiction region and dynamic friction, which consists of Stribeck effect, Coulomb friction and viscous friction.…”
Section: Nonlinear Friction Forces Modelmentioning
confidence: 86%
“…The dynamic equation of motion for the mass body test rig with the consideration of the friction forces for PS system, as previously researched by Alzughaibi et al, 1 is…”
Section: Ps Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…If excessively large vibrations are transferred to the passenger space, they may cause discomfort and may be harmful to the health of drivers and passengers [12,14]. For many years, there have been attempts to provide for the best isolation of drivers and passengers from road conditions, by developing high damping coefficient shock absorbers [3,11,14]. In addition, through the construction and characteristics of shock absorbers and springs in suspensions, the goal is to decrease the frequency and amplitude of vibrations [4,7,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, such systems have disadvantages compared to passive systems, since they present issues on cost, complexity and reliability [14][15][16][17], what still secures a wide use of passive systems for cheaper cost and reliable performance [18]. In order to make passive systems achieve a comparable level of comfort, many recent studies focus on damping properties [6,17,[19][20][21][22][23] or modified constructions [1,14,15,24], where all studies achieve a better suspension ride. More expressive results achieved a 31% reduction in sprung mass acceleration by using asymmetrical dampers [19]and obtained 20% of sprung mass acceleration reduction by the change in the bleed orifice area of the inside piston [1].…”
Section: Introductionmentioning
confidence: 99%